Optimization of Perico (Coryphaena hippurus) gelatin hydrolysis process to obtain bioactive peptides by response surface modeling - Hurtado Saldaña, Diana Cecilia; Marquina Sanchez, Viviana Gisella; Ruiz Cordova, Josemaria Mathieu; Ñontol Ascate, Angel Aaron; Javier Sanchez, Jhan Pierre; Carlos Garcia, Arliss Alinzon; Silva Chuquipoma, Diego Honorato (LACCEI, 2024)
Enzymatic hydrolysis was applied following the response surface model with the objective of maximizing the degree of hydrolysis and the antioxidant activity of gelatin hydrolysates from parakeet (Coryphaena hippurus) skin. Two pretreatments were carried out which served to condition the samples prior to obtaining the gelatin. The alkaline endoprotease type enzyme Corolase 8000 (AB Enzymes) was used for gelatin extraction. In addition, the same process was optimized by maximizing variables such as time X1 (120, 240 and 360 min) and enzyme percentage Y2 (3.60, 7.20 and 14.50% w/w). The degree of hydrolysis was determined by the macro-Kjeldahl procedure, as well as the percentage of free amino groups, following the proposed equations, and the antioxidant activity was analyzed by the ABTS radical scavenging ability method. Finally, it was evidenced that the highest percentage of enzyme: substrate concentration (14.50%) at a time of 6 hours showed the maximum value of percentage of degree of hydrolysis (%DH) and for the antioxidant activity there was inhibition of the radical up to a maximum of 49.49 (μM eq. Trolox/g d.w.) at the end of 6 hours, showing a significant difference with respect to the control sample (34.58 μM eq. Trolox/g d.w.). Therefore, it was concluded that the enzymatic hydrolysis parameters allowed enhancing the biological characteristics of fish gelatin.